Robust highly flexible all-solid-state micro pseudocapacitor based on ternary oxide CuCo2O4 having ultrathin porous nanowall type morphology blended with CNT - Basu, Aniruddha; Bhardwaj, Monika; Gawli, Yogesh; Rode, Chandrasekhar V.; Ogale, Satishchandra B. (Chemistryselect, 2016)
In this work we demonstrate a facile approach to the fabrication of all solid state flexible interdigitated micro pseudocapacitor device using pre-synthesized CuCo2O4 (CCO) ternary metal oxide as the electrode material. The hydrothermally synthesized CCO exhibits a peculiar 3D interconnected aligned porous nanowall type morphology which is highly desirable for storage as well as charge transfer. The device is fabricated using CO2 laser scribing technique and the PVA-H3PO4 gel electrolyte is used as the electrolyte. The as-synthesized CCO as well as its blend with 10 wt.% CNT are examined for the electrochemical performance. CNT blending is shown to reduce the charge transfer resistance dramatically, thereby enhancing the pseudo capacitance. The areal capacitance of 2.29 mF cm(-2) is obtained from the solid state device. Moreover, the CCO-CNT electrode also shows a high stability upto 9000 cycles without a sign of further decay. Importantly, the devices also retain over 65% of their initial capacitance after 1000 large angle (608) bending cycles and 93% of the initial capacitance under 1208 bending condition, thanks to the mechanical flexibility afforded by CNTs without disrupting conducting paths.